2022
DOI: 10.1155/2022/2136807
|View full text |Cite|
|
Sign up to set email alerts
|

Pueraria lobata Targeted Preparation Improves the Clinical Symptoms of Cervical Spondylosis by Regulating the Balance of Gut Microbiota

Abstract: Background. Nanotargeted preparations can enhance the safety and effectiveness of medication by altering the pharmacokinetic behavior of drugs in the human body, and Pueraria lobata is shown to be effective in the treatment of neck and back pain. Purpose. This study prepared a nano-Pueraria targeted preparation, in order to analyze its effect on improving the clinical symptoms of cervical spondylosis by adjusting the balance of intestinal flora. Methods. A total of 200 patients with cervical spondylosis admitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Recent studies propose a potential relationship between the gut microbiota and the development of SP. Patients with NP exhibited higher levels of Bacteroidetes and Proteobacteria and significantly lower levels of Firmicutes compared to healthy controls ( Qin, 2022 ). Similarly, individuals with BP showed a distinct gut microbiota composition, characterized by elevated concentrations of Adlercreutzia , Roseburia , and Uncl.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies propose a potential relationship between the gut microbiota and the development of SP. Patients with NP exhibited higher levels of Bacteroidetes and Proteobacteria and significantly lower levels of Firmicutes compared to healthy controls ( Qin, 2022 ). Similarly, individuals with BP showed a distinct gut microbiota composition, characterized by elevated concentrations of Adlercreutzia , Roseburia , and Uncl.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%